Discursos e representações sobre identidades territoriais nas políticas de turismo em Goiás - Gonçalves, Leonardo Ravaglia Ferreira (2018)
The concept of territory comprehends a multiplicity of ideas that can not be considered homogeneous, evidencing the clashes and tensions that permeate social relations as a whole. If the territory is the space of mediation of the power relations, the territorial identity situates as a discursive practice of these social agents and the way in which this practice legitimize historically. The territorial identities are built along the domain and space appropriation relations, on the special power mediations, and can be produced ideologically, with internal and external influences, through speeches of social agents with higher influence power. Therefore, it is possible for the territorial identities to be more related to the designated space than the one effectively lived, not being forged equally by the several social groups. The state, political arena par excellence in which the relations of power are realized, seeks to acquire legitimacy in its existence through the repetition of discourses, manipulation of imaginaries and, consequently, of an identity. The public tourism policies are inserted in this discussion to the extent in which they are being used to shape the image of a region, highlight characteristics of the territory, reproduce hegemonic discourses and, thus, alter the perception of territorial identity. The state of Goiás has a tourism policy aligned with the rules of the Ministry of Tourism, managed by institutions that have their own interests, and explicit a way of interpreting the phenomenon of tourism, ideologically influenced. Thus, the general objective of this thesis is to analyze how the public policies of tourism in Goiás influenced, and influence, the consolidation of a territorial identity of Goiás. In order to achieve this goal, we perform theoretical research through a bibliographical survey, using notably the cultural geography approach, starting from the theoretical discussion of territory and entering other concepts in the legitimation of discourses and the construction of representations. Secondly, we study the process of identity formation of the state of Goiás through the historical analysis of the construction of symbolic-identity processes in the state. We then go into the history of public tourism policies in Goiás and Brazil, analyzing official documents, pertinent legislation and other authors that have similar studies. With this information, we went to the analysis of the materials of tourist disclosure of the state and, lastly, the interviews conducted with tourism managers in Goiás. Three groups were interviewed: the tourism managers from the municipalities, from Goiás Turismo and from Support to Micro and Small Businesses (SEBRAE), which has great influence in the formulation of tourism policies in the state. Among the results of the research, we conclude that public tourism policies interfere with and influence the identity conception of Goiás, shaped accordingly to the noticed by the potential client, independently if it corresponds to the lived.